Electronic-Based Government Systems, Institutional Capacity Building, and Public Service Performance in Ambon City - Revaalya Nurlatu; Stanislaus Kostka Ohoiwutun; Julia Theresia Patty (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study analyzes the influence of the Electronic-Based Government System (SPBE) and human resource capacity on employee performance at the Office of Communication, Informatics, and Encryption of Ambon City, while interpreting both variables as part of institutional capacity building and social learning in digital governance reform. Methodology: A quantitative survey approach was used. Data were collected through closed-ended questionnaires distributed to all 21 employees and analyzed using validity, reliability, classical assumption, multiple regression, t-test, F-test, and coefficient of determination procedures. Main Findings: SPBE implementation and human resource capacity have positive and significant effects on employee performance, both partially and simultaneously. SPBE strengthens coordination, data transparency, administrative efficiency, and service responsiveness, while human resource capacity supports digital literacy, adaptability, problem solving, and institutional learning. Novelty/Originality of this study: This study reframes SPBE as a socio-technical system and human resource capacity as collective learning within local government. It connects quantitative performance analysis with the social dynamics of decentralized digital governance in Eastern Indonesia.